Do employers discriminate less if vacancies are difficult to fill? Evidence from a field experiment - Stijn Baert; Bart Cockx; Niels Gheyle; Cora Vandamme (Institute for the Study of Labor (IZA), 2013)
We empirically test the relationship between hiring discrimination and labour market tightness at the level of the occupation. To this end, we conduct a correspondence test in the youth labour market. In line with theoretical expectations, we find that, compared to natives, candidates with a foreign sounding name are equally often invited to a job interview if they apply for occupations for which vacancies are difficult to fill, but they have to send twice as many applications for occupations for which labour market tightness is low. Our findings are robust against various sensitivity checks.
Keywords: C93; J15; J21; J24; J42; J71; 330; hiring discrimination; ethnic discrimination; labour market tightness; field experiments